Motif Penggunaan Aplikasi Tik Tok oleh Siswa Madrasah Aliyah Negeri (MAN), Kota Pariaman - Elfina Elfina; Hermawati Hermawati; Arifah Yenni Gustia; Sheiful Yazan; Abdullah Khusairi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
TikTok is short video application with increasing users since 2016 especially when Covid-19. On July 3, 2018 the Ministry of Communication and Information blocked TikTok because app abuse, pornographic content, immoral content, religion harassement and others. But, the blocking don’t have impact to number of TikTok users in Indonesian and this proves if TikTok interesting for TikTok users. This is descriptive research with qualitative-quantitative method, and motive for using media as single variable. Use gratification sought and gratification obtained theory and MAN Kota Pariaman student as subject, data analysis techniques on this research use TCR to know motive of respondent to using TikTok as a social media. The results of study show if MAN Kota Pariaman Student have cognitive motive, diversion motive and personal identity motive in using TikTok app